IMPROVING THE VIRTUAL LEARNING DEVELOPMENT PROCESSES USING XML STANDARDS - Suss, Kurt; Oberhofer, Thomas (International Journal of English Studies, 2002)
Distributed Icarning environments and content often lack a common basis for the cxchange of learning materials. This delays, or even hinders, both innovation and delivery of learning tecnology. Standards for platforms and authoring may provide a way to improve interoperability and cooperative development. This article provides an XML-based approach to this problem creaied by the IMS Global Learning Consortium.